Gender perspectives in community-based natural resource utilization and management in Pandin Lake, San Pablo City, Laguna, Philippines - Anastacio, Nico Jayson C.; Paunlagui, Merlyne M.; Janiya, Karen S. (2018)
This study provides a gender perspective on the utilization and management of natural resources in Pandin Lake, particularly in relation to fisheries production and ecotourism. Findings primarily indicat- ed both differences and similarities between local men and women as regards their knowledge, atti- tude, and perception on the natural endowments of the lake, as well as in the identified pressing issues, challenges, and needs that could affect lake management and local livelihood. Such similarities and differences as viewed from the gender lens make the case for the need to strengthen the gender per- spective in current management and development plan of the lake. This could consequently result in a more appropriate and effective design of programs, projects, and activities for the local community, which could ultimately promote sustainability and conservation of the lake and its natural resources.
Keywords: Community Based Natural Resource Management